2021
DOI: 10.1002/pc.25959
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocating friction and wear performances of nanometer sized‐TiO2 filled epoxy composites

Abstract: Nanometer-sized particles, for example, TiO 2 , have gradually gained the attention to improve the mechanical and tribological properties of epoxy composite coatings. In the present paper, TiO 2 with the size of 300 nm was applied to improve the reciprocating friction and wear performances of an epoxy composite. The effects of TiO 2 content and sample preparation methods on the mechanical and tribological performances were investigated experimentally. It was found that the optimal mixture ratio of TiO 2 was 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…It is the highest point of the Y -axis in Figure 11 . The ultimate strain (elongation at break) demonstrates the ability of a material to resist shape change before finally breaking ( Tian et al, 2021 ). It is the largest value of the X -axis (strain) in Figure 11 ( Sluzalec, 1992 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is the highest point of the Y -axis in Figure 11 . The ultimate strain (elongation at break) demonstrates the ability of a material to resist shape change before finally breaking ( Tian et al, 2021 ). It is the largest value of the X -axis (strain) in Figure 11 ( Sluzalec, 1992 ).…”
Section: Resultsmentioning
confidence: 99%
“…From the physical point of view, the cracks may grow when free water molecules inside the pores change into vapor, causing a rise of internal stress inside the pores. It has been reported elsewhere that the addition of silicone materials can improve the mechanical properties of materials [ 21 ], and the addition of diphenylsilanediol may improve the ability of the material to withstand internal stress by transferring internal stress and increasing the molecules’ flexibility [ 22 , 23 ]; this means that more energy may be needed to cause stress concentration that is severe enough to break the material, thus inhibiting the generation and development of cracks and pores. These observations prove the assumption in Section 3.2 that the size of cracks and holes may play an important role in the changes of PDIV.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the mechanical properties and durability of epoxy resin can be further improved by adding some functional nanoparticles to epoxy resin. Tian et al [ 25 ] studied experimentally the effects of titania content and sample preparation methods on the mechanical performances of epoxy. They found that the tensile strength of epoxy increased by up to 30% compared with the control for the optimal mixture ratio (4%) of titania.…”
Section: Introductionmentioning
confidence: 99%